THEORETICAL FOUNDATIONS FOR THE FORMATION OF MANAGERIAL QUALITIES IN PEDAGOGICAL SPECIALISTS - Odilova Odina (Journal of new century innovations, 2024)
Annotation: this article reveals the role of pedagogical personnel today and its competence in the quality of management. The importance of these qualities in the organization of the lesson and the impact of educators on the effectiveness of the lesson were analyzed.